Enhanced glycerol assimilation and lipid production in Rhodotorula toruloides CBS14 upon addition of hemicellulose primarily correlates with early transcription of energy-metabolism-related genes - Giselle C. Martín-Hernández; Mikołaj Chmielarz; Bettina Müller; Christian Brandt; Adrian Viehweger; Martin Hölzer; Volkmar Passoth (Biotechnology for Biofuels and Bioproducts, 2023)
Abstract Background Lipid formation from glycerol was previously found to be activated in Rhodotorula toruloides when the yeast was cultivated in a mixture of crude glycerol (CG) and hemicellulose hydrolysate (CGHH) compared to CG as the only carbon source. RNA samples from R. toruloides CBS14 cell cultures grown on either CG or CGHH were collected at different timepoints of cultivation, and a differential gene expression analysis was performed between cells grown at a similar physiological situation. Results We observed enhanced transcription of genes involved in oxidative phosphorylation and enzymes localized in mitochondria in CGHH compared to CG. Genes involved in protein turnover, including those encoding ribosomal proteins, translation elongation factors, and genes involved in building the proteasome also showed an enhanced transcription in CGHH compared to CG. At 10 h cultivation, another group of activated genes in CGHH was involved in β-oxidation, handling oxidative stress and degradation of xylose and aromatic compounds. Potential bypasses of the standard GUT1 and GUT2-glycerol assimilation pathway were also expressed and upregulated in CGHH 10 h. When the additional carbon sources from HH were completely consumed, at CGHH 36 h, their transcription decreased and NAD+-dependent glycerol-3-phosphate dehydrogenase was upregulated compared to CG 60 h, generating NADH instead of NADPH with glycerol catabolism. TPI1 was upregulated in CGHH compared to cells grown on CG in all physiological situations, potentially channeling the DHAP formed through glycerol catabolism into glycolysis. The highest number of upregulated genes encoding glycolytic enzymes was found after 36 h in CGHH, when all additional carbon sources were already consumed. Conclusions We suspect that the physiological reason for the accelerated glycerol assimilation and faster lipid production, was primarily the activation of enzymes that provide energy.